Aging‐associated skeletal muscle defects in HER2/Neu transgenic mammary tumour model. Issue 1 (15th July 2020) - Wang, Ruizhong; Kumar, Brijesh; Bhat‐Nakshatri, Poornima; Prasad, Mayuri S.; Jacobsen, Max H.; Ovalle, Gabriela; Maguire, Calli; Sandusky, George; Trivedi, Trupti; Mohammad, Khalid S.; Guise, Theresa; Penthala, Narsimha R.; et al.
Abstract: Background: Loss of skeletal muscle volume and functional limitations are poor prognostic markers in breast cancer patients. Several molecular defects in skeletal muscle including reduced myoblast determination protein 1 (MyoD) levels and increased protein turn over due to enhanced proteosomal activity have been suggested as causes of skeletal muscle loss in cancer patients. However, it is unknown whether molecular defects in skeletal muscle are dependent on tumour aetiology. Methods: We characterized functional and molecular defects of skeletal muscle in mouse mammary tumour virus (MMTV)‐Neu (Neu+) mice ( n  = 6–12), an animal model that represents HER2 + human breast cancer, and compared the results with well‐characterized luminal B breast cancer model MMTV‐PyMT (PyMT+). Functional studies such as grip strength, rotarod performance, and ex vivo muscle contraction were performed to measure the effects of cancer on skeletal muscle. Expression of muscle‐enriched genes and microRNAs as well as circulating cytokines/chemokines were measured. Because nuclear factor‐kappaB (NF‐κB) pathway plays a significant role in skeletal muscle defects, the ability of NF‐κB inhibitor dimethylaminoparthenolide (DMAPT) to reverse skeletal muscle defects was examined. Results: Neu+ mice showed skeletal muscle defects similar to accelerated aging. Compared with age and sex‐matched wild type mice, Neu+ tumour‐bearing mice had lower grip strength (202 ± 6.9 vs. 179 ± 6.8 g grip force, P  = 0.0069) and impaired rotarod performance (108 ± 12.1 vs. 30 ± 3.9 s, P  < 0.0001), which was consistent with reduced muscle contractibility ( P  < 0.0001). Skeletal muscle of Neu+ mice ( n  = 6) contained lower levels of CD82 + (16.2 ± 2.9 vs. 9.0 ± 1.6) and CD54 + (3.8 ± 0.5 vs. 2.4 ± 0.4) muscle stem and progenitor cells ( P  < 0.05), suggesting impaired capacity of muscle regeneration, which was accompanied by decreased MyoD, p53, and miR‐486 expression in muscles ( P  < 0.05). Unlike PyMT+ mice, which showed skeletal muscle mitochondrial defects including reduced mitochondria levels and peroxisome proliferator‐activated receptor gamma co‐activator 1 (beta), Neu + mice displayed accelerated aging‐associated changes including muscle fibre shrinkage and increased extracellular matrix deposition. Circulating 'aging factor' and cachexia and fibromyalgia‐associated chemokine C‐C motif chemokine ligand 11 (Ccl11) was elevated in Neu+ mice (1439.56 ± 514 vs. 1950 ± 345 pg/mL, P  < 0.05). Treatment of Neu+ mice with DMAPT significantly restored grip strength (205 ± 6 g force), rotarod performance (74 ± 8.5 s), reversed molecular alterations associated with skeletal muscle aging, reduced circulating Ccl11 (1083.26 ± 478 pg/mL), and improved animal survival. Conclusions: These results suggest that breast cancer subtype has a specific impact on the type of molecular and structural changes in skeletal muscle, which needs to be taken into consideration while designing therapies to reduce breast cancer‐induced skeletal muscle loss and functional limitations.